The Etymologies of Geyon, Abbawi and Nil: The Diverse Appellations of the Blue Nile from Time Immemorial up to the Present - Bayu, Yeshambel Kindie (Ethiopian Journal of Social Sciences, 2021)
The appellation Geyon was mentioned in association with an extant name of Ethiopia. Consequently, the source area of Geyon is irrefutable. Above all, for the ancient world, Geyon/Nile was the most attractive, the most important and hence the most written about in the world. To the contrary, unlike Turkish rivers of Euphrates and Tigris, the two rivers of Ethiopia that is to say Pison and Geyon, were misrepresented by later writers as both sacred and profane. What is more, some other writers had attempted to transfer the geographical location of these rivers to other parts of the world. This happened probably either by their ignorance or by the ulterior motives of these writers. This article attempted to examine sources both secular and religious exhaustively and concluded that Pison and Geyon rise in Ethiopia and the etymologies of Geyon, Abbawi and Nil are locally derived from the classical language of Ethiopia. Keywords: Etymologies, appellations, Geyon, Abbawi, Nil